In and out of each other's bodies : theory of mind, evolution, truth, and the nature of the social. - Bloch, Maurice (Paradigm Publishers, 2013)
What is human sociality? How are universals such as truth and doubt variously demonstrated and negotiated in different cultures? This book offers an accessible introduction to these and other fundamental human questions. Bloch shows that the social consists of two very different things. One is a matter of continual adjustments between individuals who read each others' minds and thus, as in sex and birth, "go in and out of each other's minds and bodies." The other is a time defying system of roles and groups. Interaction at this level is created by ritual and is unique to humans. What is referred to by the word "religion" is a part of this, but it is not separate. The study of "religion" as such is therefore theoretically misleading. A second major theme is the way truth is established in different cultures. Bloch's arguments go against recent approaches in anthropology which have sought to relativize -- Présentation de l'éditeur.